Antifungal Evaluation of Gentian Violet and Mycostatin on Yeasts - Gardini Tuesta, W. E. (1965)
At present the diagnosis and treatment of yeast infections fungal pathogens is receiving more attention by researchers ( 1, 6 , 7, 9 , 10, 16 , 17) . In our area, genital infections yeast pathogens is common, due to treatment of bacterial infections with broad-spectrum antibiotics (4, 6, 16 ) . Other authors have noted this effect and hormonal conditions as triggers of thrush (2, 3, 5 , 6, 7 , 8, 11 , 12, 13, 18 , 19, 20 ) . In diagnostic laboratories tend to implement the use of Mycostatin discs to assess their sensitivity in the presence of yeast infection from each ; however, similar references are known about gentian violet in spite of its widespread use in therapy . The purpose of this paper is to provide a method of healthcare worker practical value to determine the sensitivity of yeast to gentian violet disk and make known the antifungal effect of the two substances are studied against yeast infections from genital .